SN 2020acat: an energetic fast rising Type IIb supernova. Issue 4 (5th May 2022) - Medler, K; Mazzali, P A; Teffs, J; Ashall, C; Anderson, J P; Arcavi, I; Benetti, S; Bostroem, K A; Burke, J; Cai, Y-Z; Charalampopoulos, P; Elias-Rosa, N; et al.
ABSTRACT: The ultraviolet (UV) and near-infrared (NIR) photometric and optical spectroscopic observations of SN 2020acat covering ∼250 d after explosion are presented here. Using the fast rising photometric observations, spanning from the UV to NIR wavelengths, a pseudo-bolometric light curve was constructed and compared to several other well-observed Type IIb supernovae (SNe IIb). SN 2020acat displayed a very short rise time reaching a peak luminosity of $\mathrm{{\rm Log}_{10}}(L) = 42.49 ± 0.17 \, \mathrm{erg \, s^{-1}}$ in only ∼14.6 ± 0.3 d. From modelling of the pseudo-bolometric light curve, we estimated a total mass of 56 Ni synthesized by SN 2020acat of M Ni = 0.13 ± 0.03 M⊙, with an ejecta mass of M ej = 2.3 ± 0.4 M⊙ and a kinetic energy of E k = 1.2 ± 0.3 × 10 51 erg. The optical spectra of SN 2020acat display hydrogen signatures well into the transitional period (≳ 100 d), between the photospheric and the nebular phases. The spectra also display a strong feature around 4900 Å that cannot be solely accounted for by the presence of the Fe ii 5018 line. We suggest that the Fe ii feature was augmented by He i 5016 and possibly by the presence of N ii 5005. From both photometric and spectroscopic analysis, we inferred that the progenitor of SN 2020acat was an intermediate-mass compact star with an M ZAMS of 15–20 M⊙ .